APLIKASI GAME KAHOOT DALAM BELAJAR UNTUK MENINGKATKAN KEGIATAN BELAJAR SISWA DALAM MAINKAN PELAJARAN IMAN KEPADA RASUL ALLAH - Fauzih, Hayi; Puadah, Popi; Hasanah, Siti Uswatun; Luthfi, Attabik; Rasyid, Hamdan (Journal of Islamic Education Studies, 2022)
Based on observations that have been made at SMP Karya Budi Cileunyi Bandung, the problem found is the low learning activity of students in PAI subjects. The low level of student learning activity is caused by various factors, namely the use of inappropriate and inappropriate learning methods or media, so that students cannot easily understand and master the material presented. The method that will be used is to apply the kahoot game which aims to be able to improve and improve the quality of teachers in the PAI learning process on the material of faith in Allah's Apostle. Specifically, the purpose of this study was to find out the results of student learning activities before implementing the kahoot game in PAI learning, to find out the process of implementing the kahoot game in PAI learning by observing the activities of teachers and students, and to determine the increase in the results of student learning activities after the implementation of the kahoot game in learning PAI. This kahoot game application emphasizes learning styles that involve the role of student learning activities through competitive participation with their peers in the learning they are studying and learning. This type of research is Classroom Action Research (CAR). The method of data collection is observation with observation sheets and documentation. The data analysis used is descriptive qualitative. The results of data analysis showed that the percentage of student learning activities before using the Kahoot game in PAI learning. So it can be concluded that the implementation of PAI learning by using kahoot games can improve student learning activities.